The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3325/cmj.2017.58.270
|View full text |Cite
|
Sign up to set email alerts
|

A combination of levobupivacaine and lidocaine for paravertebral block in breast cancer patients undergoing quadrantectomy causes greater hemodynamic oscillations than levobupivacaine alone

Abstract: AimTo test for differences in hemodynamic and analgesic properties in patients with breast cancer undergoing quadrantectomy with paravertebral block (PVB) induced with a solution of either one or two local anesthetics.MethodA prospective, single-center, randomized, double-blinded, controlled trial was conducted from June 2014 until September 2015. A total of 85 women with breast cancer were assigned to receive PVB with either 0.5% levobupivacaine (n = 42) or 0.5% levobupivacaine with 2% lidocaine (n = 43). Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“… 6 A previous clinical study also revealed that the application of ultrasound-guided paravertebral block was unsuccessful in 5–10% of cases. 7 This failure rate is similar to the rate observed in paravertebral block using the classic landmark technique. 8 , 9 A substantial improvement in reliability is needed, and thus, we devised the pressure measurement method during needle advancement of TPVB.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“… 6 A previous clinical study also revealed that the application of ultrasound-guided paravertebral block was unsuccessful in 5–10% of cases. 7 This failure rate is similar to the rate observed in paravertebral block using the classic landmark technique. 8 , 9 A substantial improvement in reliability is needed, and thus, we devised the pressure measurement method during needle advancement of TPVB.…”
Section: Introductionsupporting
confidence: 76%
“… 15 , 16 The studies in human cadavers and human patients also showed that the application of ultrasound-guided TPVB was unsuccessful in 4–7% of cases. 4 7 A potential explanation for the unsuccessful results is the technical difficulty, even under ultrasound guidance, that can occur with potential image loss when the needle tip is advanced to the adjacent transverse process. 4 , 5 Therefore, we tried to improve the accurate placement of the needle tip by combining a pressure measurement method with an ultrasound-guidance approach while also intending to assess the analgesic efficacy through this more delicate technique.…”
Section: Discussionmentioning
confidence: 99%
“…The time required to perform a single‐injection paravertebral block was shorter compared with the multiple‐injection group (5 min vs. 10 min; median difference 4 min; 95%CI ‐6 to ‐3 min; p < 0.001) . Ultrasound guidance was used to perform paravertebral injections or catheter positioning in eight studies , whereas 16 other studies did not use ultrasound . The results were not different depending on the use of ultrasound guidance or not.…”
Section: Resultsmentioning
confidence: 94%
“…Unilateral application can be conducted on one or more vertebral levels, with or without catheter insertion ( 5 , 8 , 10 , 12 , 24 ). Bilateral application is most commonly a single shot technique on two levels, depending on the type of surgery, in order to avoid potential complications (local anaesthetic toxicity and haemodynamic instability) ( 5 , 8 , 10 , 12 , 25 ). Unilateral application is used in breast surgery, thoracic surgery, cardiac pacemaker insertion, rib fractures, open cholecystectomy, liver resections, oesophageal and gastric surgery, partial or complete nephrectomies, inguinal herniorraphy ( 5 , 7 , 8 , 10 , 12 , 13 , 15 - 18 , 23 ).…”
Section: Discussionmentioning
confidence: 99%